ELM CULTIVATION IN MODERN ENVIRONMENTAL CONDITIONS - Izmuratova, Gulzira Duysenbayevna; Gulimatova, Diyora Davronbekovna; Saparniyazov, In’omjan Artiqbaevich (SCIENCE and SOCIETY, 2026)
This article studies the ecological and sanitary-hygienic significance of ornamental trees in urban and suburban environments, especially the ecological properties of the common elm, soil salinity and water regime, and reproduction possibilities. The experiment was conducted in the Takhtakopir district of the Republic of Karakalpakstan, and the impact of common elm on the soil water regime, as well as the technology of planting seedlings, seed dispersal, and the prospects for reproduction of this tree were discussed by assessing the germination and germination of seeds.
Keywords: ornamental tree; common elm; soil salinity; seed; seedling